Local Volume Table of prosopis Juliflora for Timber and Small Wood/firewood - Negi, M. S.; Banwal, N. R.; Srivastava, R. N. (Indian Forester, 1998)
The present study of Prosopis juliflora reflects the importance of fast growing species that will be of multipurpose character. One of the reasons for its acceptance is its adapability to semi-arid wastelands , fulewood and in the manufacturing of wide range of small and medium sized farm implements. An attempt has been made to determine the quantum of firewood that can be made available.